2023
DOI: 10.3390/ijms24043203
|View full text |Cite
|
Sign up to set email alerts
|

Fetuin-A: A Novel Biomarker of Bone Damage in Early Axial Spondyloarthritis. Results of an Interim Analysis of the SPACE Study

Abstract: Background: Our study aimed to evaluate the association between fetuin-A levels and the presence of radiographic sacroiliitis and syndesmophytes in patients with early axial spondyloarthritis (axSpA) and to identify potential predictors of radiographic damage in the sacroiliac joints (SIJs) after 24 months. Methods: Patients diagnosed with axSpA in the Italian cohort of the SpondyloArthritis-Caught-Early (SPACE) study were included. Physical examinations, laboratory tests (including fetuin-A), SIJ,+ and spinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The associations of the genetic prediction of B vitamins and Hcy concentrations with total body BMD and BMD in different age strata are displayed in Figure 4. We observed the significant associations of genetically predicted elevated vitamin B12 with lower total body BMD (Beta, -0.083; 95%CI, -0.126 to -0.040; P = 1.65E-04), especially decreased total body BMD of age [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]95%CI, to -0.067; P = 9.86E-05) and age over 60 years (Beta, -0.074; 95%CI, -0.141 to -0.007; P = 0.031). No significant association was revealed in Hcy and other B vitamins with total body BMD in different age strata (Figure 4, Effects of the genetic prediction of circulating vitamin B12, homocysteine, folate, and vitamin B6 on bone mineral density in different body regions and different age strata with the inverse variance weighting method.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The associations of the genetic prediction of B vitamins and Hcy concentrations with total body BMD and BMD in different age strata are displayed in Figure 4. We observed the significant associations of genetically predicted elevated vitamin B12 with lower total body BMD (Beta, -0.083; 95%CI, -0.126 to -0.040; P = 1.65E-04), especially decreased total body BMD of age [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]95%CI, to -0.067; P = 9.86E-05) and age over 60 years (Beta, -0.074; 95%CI, -0.141 to -0.007; P = 0.031). No significant association was revealed in Hcy and other B vitamins with total body BMD in different age strata (Figure 4, Effects of the genetic prediction of circulating vitamin B12, homocysteine, folate, and vitamin B6 on bone mineral density in different body regions and different age strata with the inverse variance weighting method.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Cochran's Q statistic and the MR-Egger and MR-PRESSO approaches indicated no heterogeneity and no pleiotropy existing in these analyses (Supplementary Tables 6, 7). In the multivariable MR analysis, the genetic prediction of increased vitamin B12 was more significantly associated with lower total body BMD (Beta, -0.085; 95%CI, -0.133, -0.038; P = 4.39E-04), total body BMD of age [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]95%CI,.058; P = 3.55E-04), and age over 60 years (Beta, -0.076; 95% CI, -0.145, -0.008; P = 0.029) after adjusting for education attainment, smoking, and alcohol usage (Supplementary Figure 1). Leave-one-out analysis showed that a single SNP was unable to influence the significant associations, confirming these significant results (Supplementary Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this respect, Favero et al. ( 53 ) have suggested that fetuin-A levels could be a useful biomarker for identifying axSpA patients with a high risk of developing severe disease and early structural damage.…”
Section: Discussionmentioning
confidence: 99%